Effect of Foreign Currency Translation on Performance of Selected Manuafacturing Firms in Nigeria - Olaoye, Cement Olatunji; Olaniyi , Adebusoye (The Journal of Accounting and Management, 2023)
The study evaluated the effect of foreign currency translation on the performance of selected manufacturing firms in Nigeria. Specifically, the study evaluated effect of exchange rate, transaction rate and interest rate on profit after tax of selected manufacturing firms in Nigeria. In a bid to accomplish this, panel regression analysis of fixed and random effect on ten (10) selected manufacturing firms in Nigeria were incorporated. The study employed secondary data; the data for the study covered the period 2013 to 2022. The Hausman test carried out showed that fixed effect model is more realistic and produced a better result which was therefore employed in drawing inferences in the study. From the result, exchange rate exhibited significant negative relationship; Interest rate has insignificant positive relationship, while the translation rate indicated insignificant negative relationship with selected manufacturing firms, performance in Nieria. Hence, the study concluded that unfavourable movement and adjustment in foreign currency translation rate affect the performance of selected manufacturing firms in Nigeria, especially, when measured performance in term of profit after tax (PAT). It was recommended that manufacturing firms should develop a mechanism to hedge against foreign exchange rate exposure caused by unanticipated movement in the exchange rate. More so, this should be supported by sound risk management strategies that can withstand macroeconomic instability especially inflation rate in the host economy.